(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Sumardi, Basyuni M, Wati R. 2018. Antimicrobial activity of polyisoprenoids of sixteen mangrove species from North Sumatra, Indonesia. Biodiversitas 19: 1243-1248. Mangroves including those that are distributed in the coast of North Sumatra contain polyisoprenoid with varying levels of polyprenol and dolichol constituents. Differences in polyisoprenoid levels were closely related to the salinity of sea but the information about their biological activities is scarce. The present study aimed to describe the biological activities, antimicrobial, antioxidant, and antifungal effects of polyisoprenoid extracts from sixteen mangrove species of North Sumatra, Indonesia. Polyisoprenoids were isolated from mangrove leaves and tested for their antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Candida albicans. Meanwhile, their antioxidant activity was represented by their capacity in scavenging DPPH (2,2-diphenyl-1-picrylhydrazyl) free-radical agents. The most predominant polyisoprenoids found in sixteen mangrove leaf extracts was dolichols (75%). Polyprenols-dominant species, Acacia auriculiformis, Hibiscus tiliaceus, Pongamia pinnata, and Ricinus communis, and dolichols-dominant species, Avicennia lanata, Av. marina, Av. officinalis, Barringtonia asiatica, Bruguiera gymnorrhiza, Calophyllum inophyllum, Nypa fruticans, and Pandanus odoratissimus, inhibited the growth of E. coli and S. aureus. However, the antioxidant activity of those sixteen mangrove species was of a weak category. Surprisingly, all other mangroves polyisoprenoid extracts did not inhibit C. albicans growth. This study suggested that polyisoprenoids in mangroves have potential antibacterial properties to be developed further.